Epidemiology and Clinical Outcome of Patients Hospitalized With Pelvic Inflammatory Disease Complicated by Tubo-Ovarian Abscess. Issue 4 (1995) - Chan, Ying; Parchment, Winsome; Skurnick, Joan H.; Goldsmith, Laura; Apuzzio, Joseph J.
Abstract : Objective: The purpose of this retrospective study was to compare the clinical outcome and characteristics of pelvic inflammatory disease (PID) complicated by tubo-ovarian abscess (TOA) with PID without TOA. Methods: Chart reviews were performed for all PID admissions to the University of Medicine and Dentistry of New Jersey-University Hospital, Newark, NJ, from January 1, 1992, to December 31, 1993. Results: The incidence in this study of TOA based on sonographic evidence of a complex adnexal mass was 18%. The major differences between the patients with and without TOAs were 1) history of hospitalization for PID: 68% (13/19) vs. 29% (25/85); 2) increased erythrocyte sedimentation rate: 82 vs. 41 mm/h; 3) increased WBC count on admission: 16, 200 vs. 14, 700/ml; 4) failure to respond to initial antibiotic therapy; and 5) longer hospital stay: 7.8 vs. 4.4 days, respectively. Surgical intervention was required in 3 patients: 2 patients who had TOAs and 1 patient who did not have a TOA by clinical examination or by ultrasound. Conclusions: Despite longer hospital stays and blood tests suggesting more severe disease processes, PID complicated by TOA is usually responsive to intravenous (IV) antibiotic therapy without the need for surgical intervention.